2007
DOI: 10.1016/j.atherosclerosis.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus on Chromosome 19 for circulating levels of intercellular adhesion molecule-1 in Mexican Americans

Abstract: Circulating soluble intercellular adhesion molecule-1 (sICAM-1) is a biochemical marker of inflammation. We performed variance-components-based quantitative genetic analyses in SOLAR of sICAM-1 in 1170 individuals from Mexican American families in the San Antonio Family Heart Study. The trait is heritable (h 2 = 0.50±0.06, P<10 -6 ). Multipoint linkage analysis using a ∼10-cM microsatellite map revealed a region on Chromosome 19p near marker D19S586 showing strong evidence of linkage for sICAM-1 (empirically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These results were subsequently replicated in large-scale genomics studies from Barbalic [6] et al and Qi [7] et al Nevertheless, the total variance explained by these associations remained low (8.4%) as compared to the relatively high heritability estimates (from 0.34 to 0.59) [8], [9] for sICAM-1. We therefore hypothesized that other, weaker, common genetic determinants of sICAM-1 remained to be discovered.…”
Section: Introductionmentioning
confidence: 73%
“…These results were subsequently replicated in large-scale genomics studies from Barbalic [6] et al and Qi [7] et al Nevertheless, the total variance explained by these associations remained low (8.4%) as compared to the relatively high heritability estimates (from 0.34 to 0.59) [8], [9] for sICAM-1. We therefore hypothesized that other, weaker, common genetic determinants of sICAM-1 remained to be discovered.…”
Section: Introductionmentioning
confidence: 73%
“…Several studies subsequently narrowed down the genetic determinants of circulating sICAM1 levels to the ICAM cluster on chromosome 19 with a heritability estimate from 0.34 to 0.59 [7, 8], and many single nucleotide polymorphisms (SNPs) in the vicinity of the ICAM1 locus were identified to associate with sICAM1 levels [7, 911]. We have previously reported that the ICAM1 SNP rs5491 was associated with sICAM1 levels and metabolic syndrome in a Taiwanese population [12].…”
Section: Introductionmentioning
confidence: 99%
“…39 Linkage analysis detected evidence of linkage to diabetic nephropathy on chromosomes 7q21.3, 10p15.3, 14q23.1, and 18q22.3 and to albuminuria on 2q14.1, 7q21.1, and 15q26.3 (unpublished data). Several genome-wide linkage analyses were performed to identify chromosomal regions for CVD risk in the SAFHS 40 . These include leptin concentrations (chromosome 2), 28 cholesterol concentrations in low-density lipoprotein cholesterol size fractions (chromosomes 3 and 4), 41 BMI (chromosome 8), 42 and fasting serum insulin concentrations (chromosome 3).…”
Section: Discussionmentioning
confidence: 99%